Case Report: Intraarticular Iliopsoas Tendon causes Groin Pain Following Periacetabular Osteotomy - Gebhardt, Sebastian; Nonnenmacher, Lars; Wassilew, Georgi I.; Zimmerer, Alexander (Frontiers in Surgery, 2022)
A 43-year-old female patient reported persistent iliopsoas-related groin pain following periacetabular osteotomy (PAO) combined with a femoroplasty via a direct anterior approach due to CAM morphology. Concomitantly with the planned removal of screws, hip arthroscopy was performed, and the iliopsoas tendon was found to run intraarticular, resulting in the tendon being impaired in its mobility and being entrapped. The tendon was arthroscopically released. The patient reported relief of groin pain after the arthroscopic tendon debridement. During PAO combined with capsulotomy, the postoperatively observed intraarticular position of the iliopsoas tendon should be prevented by careful closure of the joint capsule.